2016
DOI: 10.1007/s00330-016-4459-3
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility proof for high-resolution low-dose photon-counting CT of the breast

Abstract: • Photon-counting detector technology allows for spatial resolution better than 100 μm. • pcBCT allows for dose levels in the screening mammography range. • pcBCT provides the highest quality imaging of microcalcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 8 publications
0
84
0
Order By: Relevance
“…In this previous study, it has been demonstrated that the system can achieve a spatial isotropic resolution of better than 5 line pairs/mm corresponding to better than 100 μm resolution, with low noise level and under the maximal permitted level of dose exposition. 15 The high resolution, but also the possibility to evaluate the images in different planes, increases and facilitates the characterization of lesions regarding suspicious features such as conspicuity, calcifications, and asymmetries, as well as masses. 14,22,23 Due to the retrospective nature of our study, no mammography was performed in addition to B-CT, and previous mammography was available only in a limited number of cases, thus precluding a systematic 2 1 5555 5 5 4444 3 3 4545 3 3 4444 3 3 2 5555N M N M4455N M N M5545N M N M5444N M N M 3 5555 5 5 4455 4 4 4444 4 4 5544 3 3 4 5555N comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this previous study, it has been demonstrated that the system can achieve a spatial isotropic resolution of better than 5 line pairs/mm corresponding to better than 100 μm resolution, with low noise level and under the maximal permitted level of dose exposition. 15 The high resolution, but also the possibility to evaluate the images in different planes, increases and facilitates the characterization of lesions regarding suspicious features such as conspicuity, calcifications, and asymmetries, as well as masses. 14,22,23 Due to the retrospective nature of our study, no mammography was performed in addition to B-CT, and previous mammography was available only in a limited number of cases, thus precluding a systematic 2 1 5555 5 5 4444 3 3 4545 3 3 4444 3 3 2 5555N M N M4455N M N M5545N M N M5444N M N M 3 5555 5 5 4455 4 4 4444 4 4 5544 3 3 4 5555N comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on preliminary studies, all examinations were performed with a tube current of 25 mA with the aim to keep radiation dose at similar level to screening mammography. 15,16 For image reconstructions, a Feldkamp-type filtered back-projection algorithm was used by the nu:view reconstruction software. A smooth kernel (300 μm 3 ) voxel size and 4 Â 4 detector binning were used for ST image reconstruction.…”
Section: Dedicated Breast Ct Systemmentioning
confidence: 99%
“…8) compares relatively well with the resolution (1.4 lp/ mm) of the first two generations of the UC Davis CT scanners (their Bodega and Cambria systems 56 ), but lower than the latest generation scanner (their Doheny system (3.6 lp/mm 56 )), and the system that utilizes a photon counting x ray detector constructed by the Erlangen group operated in "standard mode" (2 9 2 detector binning) (1.4 lp/mm). 32 The resolution is moderately lower than the FDA-approved scanner (1.6 lp/mm 57 ). Our system's resolution is much lower than the Erlangen group's scanner operated in "lCa mode", which utilizes 1 9 1 detector binning and a high-resolution reconstruction kernel (5.3 lp/mm 32 ) and the phase-contrast scanner developed by the University of Napoli group that utilizes synchrotron radiation (6.4 lp/mm).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it highlights the many combinations of modalities, including several promising combinations that could bring QMIB into the clinic (Table 3). 27,60,72,99,113…”
Section: Quantitative Multiscale Imaging Of the Breast Modalitiesmentioning
confidence: 99%
“…115 By comparison, μCT has not yet reached breast imaging clinically due to technological and radiation dose limitations. 115 Several groups are addressing these issues with new systems that can perform whole-breast μCT; 50,60,62 however, they impart radiation dose 2× to 3× that produced from clinical mammography or digital breast tomosynthesis systems. 60,116 Thus, preclinical and clinical μCT may both prove valuable tools for future QMIB studies.…”
Section: Microcomputed Tomographymentioning
confidence: 99%